2007
DOI: 10.1111/j.1439-0485.2007.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Sulfurovum sp. on the gill surfaces of Alvinocaris longirostris, a deep‐sea hydrothermal vent shrimp

Abstract: Deep‐sea hydrothermal vents are unique light‐independent ecosystems that are sustained by chemosynthetic bacteria. For many of the invertebrates inhabiting in such environments, bacteria play essential roles in both energy acquisition and detoxification of potentially toxic gases such as H2S. In this study, the bacterial flora present on the gills of Alvinocaris longirostris (Bresiliidae: Caridea), a shrimp inhabiting hydrothermal vents (1532 m depth) at the Hatoma Knoll of the Okinawa Trough, was investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 55 publications
0
31
0
Order By: Relevance
“…Finally, Sulfurovum sp. have been found to colonize the gill surfaces of the deep-sea hydrothermal vent shrimp Alvinocaris longirostris [41]. Of course, more direct experimental evidence will be necessary to find out whether PliI really plays a role in these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Sulfurovum sp. have been found to colonize the gill surfaces of the deep-sea hydrothermal vent shrimp Alvinocaris longirostris [41]. Of course, more direct experimental evidence will be necessary to find out whether PliI really plays a role in these interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic diversity along the R. exoculata life cycle was completed by using rarefaction analyses and diversity indices (Supplementary Figure S2 and Supplementary Table S1), and rarefaction curves showed that the clone libraries correctly described the epibiotic communities, excepted for the hatched eggs library (Supplementary Figure S2). In this study, Epsilonproteobacteria sequences were overwhelmingly related to sequences usually retrieved from hydrothermal invertebrates (for example, Crysomallon squamiferum (Goffredi et al, 2004); Alvinocaris longirostris (Tokuda et al, 2008); Shinkaia crosnieri (unpublished); Rimicaris exoculata gut (Zbinden and Cambon-Bonavita, 2003) and gill chamber (Polz and Cavanaugh, 1995;Zbinden et al, 2008;) and also to the MAR environment (Lost City (Brazelton et al, 2006); Rainbow (Lopez-Garcia et al, 2003); Snake Pit (unpublished)) (Figures 3a and b, and Supplementary Table S3). The main nine Epsilonproteobacteria clusters fell within the 'hydrothermal invertebratesassociated epibionts' group (Marine Group-1) (Figure 3a).…”
Section: Microscopic Observationsmentioning
confidence: 94%
“…The clade of Epsilonproteobacteria consists of many ecotypes include symbiont with marine invertebrates (Dubilier et al 2008;Tokuda et al 2008;Tsuchida et al 2010), pathogen or normal flora of animals, and free-livings (Campbell et al 2006). In this study, the 16S rRNA gene sequences of Epsilonproteobacteria from a digestive tract of the Bathymodiolus have either possibility of a feed from mixing-zone bacterial population or a member of normal flora (Egas et al 2012;Van Horn et al 2011) .…”
Section: Discussionmentioning
confidence: 99%